Transformasi Fourier Fraksional dari Fungsi Gaussian - IIN SUTRISNA; Asriadi Nasrun; Mawardi Bahri; Syamsuddin Toaha (Jurnal Matematika, Statistika dan Komputasi, 2019)
The fractional Fourier transform is one of the generalizations of ordinary Fourier transform that depend on a particular angle . In this paper we will derive the fractional Fourier transforms of a function that is well known in the field of analysis, namely Gaussian function.